Examining Advocacy Journalism on Overtourism in Bali: Bibliometrics and Content Analysis of Balebengong.id in 2024 - Ni Putu Gita Dharmayanti; Engkus Kuswarno; Efi Fadilah (INJECT (Interdisciplinary Journal of Communication), 2025)
As a popular global tourist destination, Bali faces overtourism, affecting the environment, society, and economy. This study examines how BaleBengong, a citizen journalism-based alternative media, addresses overtourism through advocacy journalism. The research aims to explore BaleBengong's role in raising the issue of overtourism and to analyze the application of advocacy journalism in articles published by BaleBengong in 2024. Using a qualitative method with content analysis and literature review, the findings reveal that Balebengong practices advocacy journalism by reframing overtourism not merely as excessive visitor numbers but as a structural issue rooted in investor-driven development and policy failures. It amplifies marginalised local voices, critiques spatial domination, and proposes culturally grounded alternatives. The role of Balebengong is not only as a critical watchdog but also as an agent of counter-hegemony and policy advocacy, offering valuable insights into the role of citizen journalism in shaping sustainable tourism futures.